Perceived key determinants of payment instrument usage: A fuzzy cognitive mapping-based approach - Santos, F.; Ferreira, F.; Zavadskas, E.; Meidute-Kavaliauskiene, I. (BAI 2016 Proceedings of the International Conference on International Conference on Business and Information, 2016)
The recent economic climate has had direct repercussions on people’s daily lives. This has occurred not only in how they use payment instruments, but is also evinced in new concerns adjacent to technological advances, security and the credibility of financial institutions. In this regard, the banking sector has had a crucial role in countries’ economic development, making it increasingly important to understand how the banking system operates and what payment instruments are available to users. Relying on specialized literature and the application of fuzzy cognitive mapping, the current study aims to understand the cause-and-effect relationships between customers’ preference factors in using payment instruments. The results show that usability aspects and security issues constitute the factors which users pay more attention to. Strengths and limitations of the study are also discussed.